Experience of 17 Cases of Tube Thoracostomy of COVID-19 Positive Patients During COVID-19 Pandemic Under Thoracic Surgery Unit of Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh - Saha, Heemel (Cardiology and Cardiovascular Medicine, 2021)
Background: Patients with COVID-19 are at risk of developing acute respiratory distress syndrome requiring invasive mechanical ventilation. Barotrauma in these patients often leads to clinically significant pneumothorax, which necessitates chest tube thoracostomy. However, given the mode of transmission of the severe acute respiratory syndrome coronavirus 2 virus and the aerosolizing nature of the procedure, special considerations and care must be taken to mitigate the exposure risks to health care personnel. This article discusses the risk mitigation strategies proposed and under review at the authors’ institution. Objective To identify and diagnosis Tube thoracostomy of COVID-19 positive patients during COVID-19 pandemic under thoracic surgery unit of Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh. Methods and materials A retrospective study was conducted in thoracic surgery unit of Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh. Seventeen patients included in our study. We included all COVID-19 cases admitted to ICU in the period between July 2020 to August 2021, requiring thoracic surgery consultation and management. Non-COVID-19 critical cases and iatrogenic pneumothorax were excluded. Results Total 17 patients required thoracic surgery consultation and management. Causes were pneumothorax: 05 cases (29.41%), traumatic hemothorax: 01 cases (5.88%), hydropneumothorax: 01 case (5.88%) and massive pleural effusion: 10 cases (58.82%). No complication after tube thoracostomy. 15 patient’s condition were improved in relation to oxygen demand and left hospital in good health and two patient died 3 days after tube thoracostomy who were in artificial ventilation and both patients had more than 81% lung involvement (fibrosis) diagnosed by CT scan of chest. The survival analysis showed improvement in patients who had